Marketing management : analysis, planning, implementation, and control - Kotler, Philip (Prentice-Hall series in marketing, 1988)
Focuses on decisions marketing managers and top management face in their efforts to harmonize the objectives and resources of the organization and the needs and opportunities of the marketplace. The book applies marketing thinking to products and services, consumer and industrial markets